International responsibility of states (theoretical and legal view) - Pevko, Stanislav (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2023)
Introduction. This article examines the theoretical and legal possibility of bringing legal relations of a public nature to the international legal responsibility of the participating state, in order to determine the actual mechanisms for the implementation of influence measures and the types of legal consequences that apply to the guarantor state of international legal norms, by analyzing the views of scientists on the issue responsibility of states, their types, the legal framework of an international nature, which regulates the issue of the mechanism and means of influence on the state. Summary of the main research results. First, the quintessence of the axiology of responsibility as a legal phenomenon and its place in international legal relations is emphasized. Also, on the basis of the study of the views of scientists, the differentiation of international responsibility was determined. Several of its types have been identified. The first type of responsibility, which occurs in cases of illegal actions in the form of violation of contractual obligations, the second type of compliance, which occurs for the commission of international crimes. Emphasis is placed on the legal regulation of responsibility for illegal acts in the field of legal obligations. The main international normative acts regulating the procedure of bringing to responsibility, ensuring peace and security in the foreign space have been analyzed. The international practice that reveals the cases of bringing to international responsibility on the example of states that participated in legal relations in violation of international legal norms is given. Conclusions. According to the results of the study, the duality of approaches to the responsibility of states was established. Conclusions were made regarding the prospects and realities of bringing the state to international legal responsibility.